Insights From fMRI Studies Into Ingroup Bias - Molenberghs, Pascal; Louis, Winnifred R. (Frontiers in Psychology, 2018)
Intergroup biases can manifest themselves between a wide variety of different groups such as people from different races, nations, ethnicities, political or religious beliefs, opposing sport teams or even arbitrary groups. In this review we provide a neuroscientific overview of functional Magnetic Resonance Imaging (fMRI) studies that have revealed how group dynamics impact on various cognitive and emotional systems at different levels of information processing. We first describe how people can perceive the faces, words and actions of ingroup and outgroup members in a biased way. Second, we focus on how activity in brain areas involved in empathizing with the pain of others, such as the dorsal anterior cingulate cortex (dACC) and anterior insula (AI), are influenced by group membership. Third, we describe how group membership influences activity in brain areas involved in mentalizing such as the medial prefrontal cortex (mPFC) and temporoparietal junction (TPJ). Fourth, we discuss the involvement of the lateral orbitofrontal cortex (lOFC) in increased moral sensitivity for outgroup threats. Finally, we discuss how brain areas involved in the reward system such as the striatum and medial orbitofrontal cortex (mOFC), are more active when experiencing schadenfreude for outgroup harm and when rewarding ingroup (versus outgroup) members. The value of these neuroscientific insights to better understand ingroup bias are discussed, as well as limitations and future research directions.